Seasonal variation in trachoma prevalence among children, District Dera Ghazi Khan of Punjab, Pakistan - Khokhar, Abdul Rehman; Tehseen Iqbal; Mujahid Hussain; Qurrat-ul Ain Rehman (Journal of the Pakistan Medical Association, 2020)
Objective: The study objective was to estimate trachoma prevalence in relation to seasonal variation among children. Methods: Study Design was cross sectional and data was collected during all seasons of the year. After randomization of population units, 10% of them were identified by lottery and 5% of them were selected and examined for active trachoma case detection by simple random sampling technique. Total number of study participants were nine thousands seven hundred and ten (n=9710) from both urban and rural population units. The study was conducted during January –December 2018 during all three seasons of the year. After clinical examination, data was entered into a questionnaire Performa, which was used as tool for data collection. A Chi-square test was applied to compare trachoma cases among different seasons and among both boys and girls. Results: Maximum burden of disease (62.4%) was reported during spring and winter season. Both spring and winter seasons have six months duration. During summer season, 37.6% (n=70) cases were reported. A highly significant (<0.01) relationship was reported between summer and spring seasons and trachoma prevalence (p < 0.01). A high prevalence was noted among female children. Conclusion: Higher prevalence of active trachoma was noted during summer season. Keywords: trachoma, seasonal variation, children, Continuous...